The change in microorganisms reproducing in bile and blood culture and antibiotic susceptibility over the years - Nuretdin Suna; Hakan Yıldız; Mahmut Yüksel; Erkan Parlak; Selçuk Dişibeyaz; Bülent Ödemiş; Onur Aydınlı; Zülfikar Bilge; Serkan Torun; Ayşe Yasemin Tezer Tekçe; İsmail Taşkıran; Nurgül Şaşmaz (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Infection in the bile tract is a major cause of bacteremia and is related to high morbidity and mortality. We examined the changes in bacteria types and antibiotic susceptibility in bile cultures and simultaneous blood cultures taken from patients who applied for endoscopic retrograde cholangio pancreatography (ERCP)/percutaneous transhepatic cholangiography (PTC) for different bile duct diseases in recent years. Materials and Methods: Bacteria types that reproduce in bile and blood cultures from patients who applied for ERCP/PTC between the years of 2007 and 2012 in our clinic were examined. All patients were evaluated together, and in addition, the periods between 2007 and 2009 (Group 1) and between 2010 and 2012 (Group 2) were compared. Results: In total, 550 patients applied to this study. There were 266 patients in Group 1 and 284 in Group 2. Reproduction occurred in 77.6% of bile cultures. In the order of frequency, these cultures consisted of Escherichia coli (32.8%), Enterococcus spp. (26.2%), and Pseudomonas aeruginosa (11%). Enterococcus spp. were determined to be higher in Group 2 than Group 1 (p<0.016). Resistance to quinolones was found in 74.1% of patients, to ampicillin in 73.2%, and to cephalosporins in an average of 61%. Vancomycin was the most susceptible antibiotic (93.4%) to gram-positives. Resistance to piperacillin-tazobactam and amikacin was higher in Group 2 than Group 1 (p=0.001 and p=0.003, respectively). Conclusion: The most frequently reproducing bacteria in the bile cultures evaluated in our hospital were Escherichia coli and Enterococcus spp. Although it was thought that the antibiotics given empirically were effective against these bacteria, there was resistancerate of 75% in our study. We determined that the first- and second-step treatment protocols must be updated.